Expression pattern of claudins 1 and 3-an auxiliary tool in predicting behavior of mucoepidermoid carcinoma of salivary gland origin - Aro, Katri; Rosa, Luiz Eduardo Blumer [UNESP]; Bello, Ibrahim O.; Soini, Ylermi; Makitie, Antti A.; Salo, Tuula; Leivo, Ilmo (Springer, 2011)
Claudins (CLDNs) are a family of membrane proteins important for permeability of tight junctions. They have also been implicated in carcinogenesis and tumor progression. We analyzed patterns of distribution and intensity of expression of CLDNs 1, 3, 4, and 7 in mucoepidermoid carcinoma (MEC) of salivary gland in 39 patients. Correlations between the expression of CLDNs, tumor grade, and survival were explored. In immunohistochemical analysis, high expression of CLDN 1 was seen in low-grade MEC, and it appeared to be a suitable auxiliary marker of good prognosis. It classified MEC similarly to histological grading in 89.7% of cases (p=0.001). High CLDN 3 expression was seen in intermediate-and high-grade MEC, while it was low in low-grade MEC. CLDN 3 intensity correctly categorized tumors into grades in 71.8% of cases (p=0.017). However, in multivariate analysis CLDN 1 and CLDN 3 did not achieve significance over tumor grade in predicting patient behavior. We conclude that analysis of staining intensities of CLDN 1 and 3 is useful as an auxiliary diagnostic and prognostic tool in patients with salivary gland MEC.
Keywords: Claudin; Tight junctions; Mucoepidermoid carcinoma; Immunohistochemistry; Head and neck; Prognostic marker